Feed pellet and corn durability and breakage during repeated elevator handling - Boac, Josephine M.; Casada, Mark E.; Maghirang, Ronaldo G. (My University, 2008)
Pelleting of animal feeds is important for improved feeding efficiency and for convenience of handling. Pellet quality impacts the feeding benefits for the animals and pellet integrity during handling. To compare the effect of repeated handling on the quality of feed pellets and corn, a 22.6‐t (1000‐bu) lot of feed pellets made from corn meal and a 25.4‐t (1000‐bu) lot of shelled corn, were each transferred alternately between two storage bins in the USDA‐ARS, Grain Marketing and Production Research Center research elevator at Manhattan, Kansas, at an average flow rate of 59.4 t/h. Samples from a diverter‐type sampler were analyzed for particle size distribution (by sieving) and durability (by the tumbling box method). The apparent geometric mean diameter of pellet samples decreased with repeated transfers, whereas the mass of accumulated broken pellets increased with repeated transfers. The percentage of broken pellets increased by an average of 3.83% with each transfer from an initial value of 17.5%, which was significantly different from the values obtained from shelled corn (p < 0.05) with an average increase of 0.38% per transfer. The durability index of feed pellets averaged 92.9% (standard deviation = 0.6%) and did not change significantly (p > 0.05) during the transfers. The durability index of shelled corn was also not significantly different during the transfers. Analysis of dust removed by the cyclone separators showed that the mass of dust < 0.125 mm was significantly less for feed pellets (0.337 kg/t of pellet mass) than for shelled corn (0.403 kg/t of corn mass).
Keywords: Breakage; Grain elevator; Repeated handling; Feed pellets; Shelled corn; Particle size